Photocuring solid electrolyte, preparation method thereof and application of photocuring solid electrolyte in electrochromic device

The solid electrolyte prepared through photocuring technology solves the problems of easy leakage and flammability of liquid electrolytes, and improves the ionic conductivity and mechanical strength of the solid electrolyte, achieving high-performance electrochromic devices.

CN119552322APending Publication Date: 2025-03-04INST OF NEW MATERIALS ZHEJIANG UNIV OF TECH PINGHU CITY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411792879.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The liquid electrolytes used in existing electrochromic devices have problems such as easy leakage, flammability, and difficulty in applying solvents to flexible devices. The amount of solvent addition of existing solid electrolytes is difficult to control, which can easily have adverse effects on the electrolyte.

Method used

The solid electrolyte is prepared by photocuring technology, and the solid electrolyte with high transparency and electrochemical stability is obtained by mixing acrylate crosslinking agent, ethylene carbonate, ionic salt, ionic liquid and photoinitiator.

Benefits of technology

It realizes the high ionic conductivity, good interface wetting, transparency and mechanical strength of solid electrolytes, improves the response time, cycle stability and safety of electrochromic devices, and is suitable for smart glasses, smart windows and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552322A_ABST
    Figure CN119552322A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemistry, and particularly discloses a photocuring solid electrolyte, a preparation method thereof and application of the photocuring solid electrolyte in an electrochromic device. The preparation method comprises the following steps: mixing an acrylate cross-linking agent, vinylethylene carbonate, ionic salt, ionic liquid and a photoinitiator to obtain an electrolyte precursor material; and then carrying out a photocuring reaction on the electrolyte precursor material to obtain the photocuring solid electrolyte. The photocuring solid electrolyte disclosed by the invention has high transparency and electrochemical stability; according to the invention, the solidification of the solid electrolyte is not influenced while the ionic salt is fully dissolved, so that the solid electrolyte has higher ionic conductivity. Compared with a liquid-state device, the compound has the advantages that the response time is not reduced, the cycling stability is not reduced, meanwhile, high safety and heat stability are achieved, and the good application prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a photocurable solid electrolyte and a preparation method thereof and application in an electrochromic device. Background Art

[0002] Electrochromism refers to the phenomenon that the optical properties (absorption, reflectivity and transmittance) of a material change reversibly under different voltages, which manifests itself as a reversible change in the color of the material on a macro scale. Electrochromic technology has a very broad application prospect and has been applied to smart windows, anti-glare rearview mirrors for cars, electronic paper and military camouflage. The electrochromic material is encapsulated in the device through certain process means. At this time, the device has an electrochromic function, so it is called an electrochromic device. After years of development, electrochromic devices have a mature device structure, namely a five-layer sandwich structure. The structure is divided into five layers: a conductive substrate layer, an electrochromic layer, an electrolyte layer, an ion storage layer and a conductive substrate layer.

[0003] The electrolyte layer is an important component of electrochromic devices, and its quality has a huge impact on the performance of the device. Nowadays, most electrochromic devices use liquid electrolytes. For liquid devices, there are problems such as easy leakage of solvents, flammability, and difficulty in application to flexible devices. These problems limit the development and application of electrochromic devices.

[0004] The use of solid electrolytes is a good way to solve the above-mentioned defects of liquid electrolytes. Its curing methods can generally be divided into thermal curing and photocuring. Unlike thermal curing processes that require a lot of heat and long curing time (which may be up to several days), photocuring is easier and requires less energy. UV curing uses the principle of ultraviolet irradiation within a certain wavelength range and strong light to cause the decomposition of photoinitiators to generate cations and free radicals, which further cause unsaturated organic compounds to produce polymerization reactions, and finally generate a cured product with a cross-linked structure. An effective way to improve processability and enhance the contact between the electrolyte and the electrochromic layer while maintaining the size of the electrolyte is to adopt an in-situ photocuring strategy. At present, most photocurable solid electrolytes use conventional solvents, such as propylene carbonate, ethylene carbonate, and 1,4-butyrolactone. Although ionic salts have good solubility in these solvents, too much solvent will cause the polymer network to be unable to fully accommodate the solvent, which will cause the solid electrolyte to be semi-solid, while too little solvent will cause less ionic salt to dissolve, resulting in low ionic conductivity of the solid electrolyte.

[0005] Therefore, developing a solid electrolyte for electrochromic devices that combines ionic conductivity, interface wettability, transparency and mechanical strength has become a research trend. Summary of the invention

[0006] In view of this, the present invention provides a photocurable solid electrolyte and a preparation method thereof and an application in an electrochromic device to solve the defects of liquid electrolytes and the problem that the amount of solvent added in existing solid electrolytes is difficult to control and easily causes adverse effects on the electrolyte.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a photocurable solid electrolyte comprises the following steps:

[0009] 1) mixing an acrylate crosslinking agent, vinyl ethylene carbonate, an ionic salt, an ionic liquid and a photoinitiator to obtain an electrolyte precursor material;

[0010] 2) The electrolyte precursor material undergoes a photocuring reaction to obtain a photocurable solid electrolyte.

[0011] Preferably, the mass ratio of the acrylate crosslinking agent, vinyl ethylene carbonate, ionic salt, ionic liquid and photoinitiator in the electrolyte precursor material is 0.3-1: 0.3-1.5: 0-0.8: 0-1: 0.05-0.6, wherein the added amounts of the ionic salt and the ionic liquid are not zero.

[0012] Preferably, the acrylate crosslinking agent is one or more of ethoxylated trimethylolpropane triacrylate and polyethylene glycol diacrylate.

[0013] Preferably, the ionic salt is lithium bis(trifluoromethanesulfonyl imide).

[0014] Preferably, the ionic liquid is 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt.

[0015] Preferably, the photoinitiator comprises 2-hydroxy-2-methyl-1-phenylpropanone and / or (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.

[0016] Preferably, the photocuring reaction is curing under ultraviolet light, the power of the ultraviolet light is 12 to 18 W, and the time of the photocuring reaction is 5 to 90 seconds.

[0017] Another object of the present invention is to provide a photocurable solid electrolyte prepared by the preparation method.

[0018] Another object of the present invention is to provide an application of a photocurable solid electrolyte in an electrochromic device, wherein the electrochromic device comprises a transparent conductive electrode 1, an electrochromic layer, an electrolyte layer, an ion storage layer, and a transparent conductive electrode 2 arranged in sequence;

[0019] The electrolyte layer is a photocurable solid electrolyte.

[0020] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention prepares a solid electrolyte with excellent performance through ultraviolet curing, which has high transparency and electrochemical stability.

[0022] 2. In the field of electrochromism, the solid electrolyte prepared by the present invention creatively uses vinyl ethylene carbonate solvent, which ensures that the ion salt is fully dissolved without affecting the solidification of the solid electrolyte, so that the solid electrolyte has a higher ionic conductivity.

[0023] 3. The present invention prepares a solid-state electrochromic device with excellent performance by using UV in-situ photocuring technology. Compared with liquid devices, the response time and cycle stability are not reduced, and the device also has high safety and thermal stability, which makes it have good application prospects in the fields of smart glasses, smart windows, car sunroofs, smart skylights, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the electrochromic device of the present invention; wherein 1-substrate 1, 2-transparent conductive layer 1, 3-electrochromic layer, 4-electrolyte layer, 5-ion storage layer, 6-transparent conductive layer 2, 7-substrate 2;

[0026] Figure 2 The electrochemical impedance spectra and physical images of the solid electrolytes prepared in Examples 1 to 4 are shown in FIG. Figure 2 a in the equation is the electrochemical impedance spectroscopy. Figure 2 b in the figure is a real picture;

[0027] Figure 3 The electrochemical impedance spectra and physical images of the solid electrolytes prepared in Examples 5 to 8 are shown in FIG. Figure 3 a in the equation is the electrochemical impedance spectroscopy. Figure 3 b in the figure is a real picture;

[0028] Figure 4 The electrochemical impedance spectra and physical images of the solid electrolytes prepared in Examples 9 to 13 are shown in FIG. Figure 4 a in the equation is the electrochemical impedance spectroscopy. Figure 4 b in the figure is a real picture;

[0029] Figure 5 The electrochemical impedance spectra and physical images of the solid electrolytes prepared in Comparative Examples 1 to 3 and Examples 14 to 18 are shown, wherein: Figure 5 a in the equation is the electrochemical impedance spectroscopy. Figure 5 b in the figure is a real picture;

[0030] Figure 6 is the absorptivity graph of the electrochromic device prepared in Application Example 1 at a wavelength of 380 to 800 nm;

[0031] Figure 7 is a response time curve of the electrochromic device prepared in Application Example 1 at a wavelength of 547 nm;

[0032] Figure 8 This is a cyclic stability diagram of the electrochromic device prepared in Application Example 1 at a wavelength of 547 nm. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a photocurable solid electrolyte, comprising the following steps:

[0034] 1) mixing an acrylate crosslinking agent, vinyl ethylene carbonate, an ionic salt, an ionic liquid and a photoinitiator to obtain an electrolyte precursor material;

[0035] 2) The electrolyte precursor material undergoes a photocuring reaction to obtain a photocurable solid electrolyte.

[0036] In the present invention, the mass ratio of the acrylate crosslinking agent, vinyl ethylene carbonate, ionic salt, ionic liquid and photoinitiator in the electrolyte precursor material is 0.3-1: 0.3-1.5: 0-0.8: 0-1: 0.05-0.6, wherein the added amount of the ionic salt and the ionic liquid is not 0, preferably 0.4-0.8: 0.5-1.2: 0.1-0.6: 0.4-0.9: 0.1-0.5, further preferably 0.5-0.7: 0.6-1: 0.2-0.5: 0.5-0.8: 0.2-0.4, and further preferably 0.6: 0.9: 0.4: 0.75: 0.35.

[0037] In the present invention, the acrylate crosslinking agent is one or more of ethoxylated trimethylolpropane triacrylate (ETPTA) and polyethylene glycol diacrylate (PEGDA).

[0038] In the present invention, the ionic salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0039] In the present invention, the ionic liquid is 1-vinyl-3-butyl imidazolium trifluoromethanesulfonyl imide (BVIMTFSI).

[0040] In the present invention, the photoinitiator includes 2-hydroxy-2-methyl-1-phenylpropanone (HMPP) and (2,4,6-trimethylbenzoyl)diphenylphosphine oxide (TPO).

[0041] In the present invention, the photocuring reaction is curing under ultraviolet light, the power of the ultraviolet light is 12-18 W, specifically 13 W, 14 W, 15 W, 16 W, 17 W; the wavelength of the ultraviolet light is preferably 356 nm; the time of the photocuring reaction is 5-90 s, specifically 10 s, 15 s, 20 s, 25 s, 30 s, 35 s, 40 s, 45 s, 50 s, 55 s, 60 s, 65 s, 70 s, 75 s, 80 s, 85 s.

[0042] The invention also provides a photocurable solid electrolyte prepared by the preparation method.

[0043] The present invention also provides an application of a photocurable solid electrolyte in an electrochromic device, wherein the electrochromic device comprises a transparent conductive electrode 1, an electrochromic layer, an electrolyte layer, an ion storage layer, and a transparent conductive electrode 2 which are arranged in sequence.

[0044] In the present invention, the electrolyte layer is a photocurable solid electrolyte.

[0045] In the present invention, the transparent conductive electrode 1 is composed of a substrate 1 and a transparent conductive layer 1; the transparent conductive electrode 2 is composed of a substrate 2 and a transparent conductive layer 2.

[0046] In the present invention, the first substrate and the second substrate are independently selected from glass, polyethylene terephthalate (PET) or polydimethylsiloxane (PDMS).

[0047] In the present invention, the transparent conductive layer 1 and the transparent conductive layer 2 are independently selected from indium tin oxide, fluorine-doped indium tin oxide and silver nanowires.

[0048] In the present invention, the electrochromic layer is selected from electrochromic conductive polymers, and specifically may be one or more of polythiophene derivatives, polytriphenylamine derivatives, polycarbazole derivatives and polypyrrole derivatives.

[0049] In the present invention, the ion storage layer is selected from poly (3,4-ethylenedioxythiophene) / polystyrene sulfonate (PEDOT:PSS), titanium dioxide (TiO2) or vanadium pentoxide (V2O5).

[0050] The preparation method of the electrochromic device is specifically as follows: attaching the electrochromic layer 3 and the ion storage layer 5 to the transparent conductive layer 1 2 and the transparent conductive layer 2 6, pasting a glue frame around the transparent conductive layer 2 6 of the transparent conductive electrode 2 including the ion storage layer 5, uniformly applying the above-mentioned solid electrolyte precursor material into the glue frame, and then covering the surface of the transparent conductive layer 1 2 of the transparent conductive electrode 1 including the electrochromic layer on the glue frame, so that the transparent conductive electrode 1 and the transparent conductive electrode 2 are attached and form a closed space with the glue frame, and finally curing under ultraviolet light to obtain a solid-state electrochromic device.

[0051] The schematic diagram of the electrochromic device prepared by the present invention is as follows Figure 1 As shown, 1-substrate one, 2-transparent conductive layer one, 3-electrochromic layer, 4-electrolyte layer, 5-ion storage layer, 6-transparent conductive layer two, 7-substrate two.

[0052] In the present invention, the thickness of the rubber frame is preferably 0.3 mm.

[0053] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] (1) Preparation of electrolyte materials:

[0056] 0.6 g of polyethylene glycol diacrylate, 0.9 g of vinyl ethylene carbonate, 0.4 g of lithium bis(trifluoromethanesulfonyl)imide, 0.75 g of 1-vinyl-3-butylimidazole trifluoromethanesulfonyl imide salt, and 0.35 g of 2-hydroxy-2-methyl-1-phenylacetone were added into a beaker, and ultrasonically mixed to obtain an electrolyte precursor material;

[0057] (2) Preparation of test device:

[0058] A glue frame was pasted around the transparent conductive layer 2 of the transparent conductive electrode 2, the above-mentioned color-changing active layer material was evenly applied into the glue frame, and then the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 was covered on the glue frame, so that the transparent conductive electrode 1 and the transparent conductive electrode 2 were attached to form a closed space with the glue frame, and finally placed under a 15W ultraviolet lamp (wavelength 356nm) for curing for 90s to obtain a test device.

[0059] The test device prepared in Example 1 was connected to an electrochemical workstation to perform an impedance test on the solid electrolyte. The test frequency was 1-100000 Hz, the AC perturbation voltage was 5 mV, and the ion conductivity was 0.00116 s / m.

[0060] The test device prepared in Example 1 was connected to an electrochemical workstation to perform an impedance test and an electrochemical stability test of the solid electrolyte. The scan rate was 10 mV / s, the test voltage was 0-5 V, and the oxidation voltage of the solid electrolyte was 2.8 V.

[0061] Embodiments 2 to 4

[0062] Compared with Example 1, some components and proportions of the electrolyte precursor materials in Examples 2 to 4 are different, and the remaining steps are the same. The different components and test results are shown in Table 1.

[0063] Table 1 Distribution ratio and test results of Example 2 to 4

[0064]

[0065]

[0066] As shown in Table 1, in the preparation method of the solid electrolyte provided by the present invention, the use of the crosslinking agent ETPTA and the photoinitiator TPO will lead to a decrease in ionic conductivity, and the results are as follows: Figure 2 As shown, Figure 2 a in the equation is the electrochemical impedance spectroscopy. Figure 2 b in the figure is a real picture (Examples 1 to 4 are respectively denoted as PEGDA-HMPP, PEGDA-IPO, ETPTA-HMPP, and ETPTA-IPO), but its effect on the oxidation voltage is not significant.

[0067] Embodiments 5 to 8

[0068] Compared with Example 1, Examples 5 to 8 have different HMPP ratios of electrolyte precursor materials, and the remaining steps are the same. The different components and test results are shown in Table 2.

[0069] Table 2 Distribution ratios and test results of Examples 5 to 8

[0070]

[0071] As shown in Table 2, in the preparation method of the solid electrolyte provided by the present invention, different amounts of HMPP used will lead to changes in ionic conductivity. Although a reduction in the amount of HMPP used will lead to an increase in ionic conductivity, the toughness of the solid electrolyte will decrease. The results are as follows: Figure 3 As shown, Figure 3 a in the equation is the electrochemical impedance spectroscopy. Figure 3b in the figure is a real picture (Examples 5 to 8 are recorded as 0.05g, 0.15g, 0.25g, and 0.45g, respectively, and Example 1 is recorded as 0.35g). Figure 3 It can be seen that if the amount of HMPP used is too small, the solid electrolyte will not be sufficiently solidified and will be fragmented. As the amount of HMPP used increases, the solidification degree and toughness of the solid electrolyte increase.

[0072] Examples 9 to 13

[0073] Compared with Example 1, Examples 9 to 13 have different light curing times, while the other steps are the same. The light curing times and test results are shown in Table 3.

[0074] Table 3 Light curing time and test results of Examples 9 to 13

[0075]

[0076] As shown in Table 3, in the preparation method of the solid electrolyte provided by the present invention, different illumination time will lead to changes in ionic conductivity. An increase in illumination time will lead to a decrease in ionic conductivity. However, if the illumination time is insufficient, the electrolyte will not be completely solidified, and if the illumination time is too long, the electrolyte will turn yellow. The results are as follows: Figure 4 As shown, Figure 4 a in the equation is the electrochemical impedance spectroscopy. Figure 4 b in the figure is a real picture (Examples 9 to 13 are recorded as 5s, 10s, 15s, 20s, and 25, respectively, and Example 1 is recorded as 90s). Figure 4 It can be seen that when the illumination time is short, the solid electrolyte is not completely cured, resulting in partial solidification in the form of fragments. As the illumination time increases, the degree of curing increases and the solid electrolyte becomes more complete.

[0077] Comparative Examples 1 to 3 and Examples 14 to 18

[0078] Compared with Example 12, Comparative Examples 1 to 3 and Examples 14 to 18 have different PEGDA ratios in the electrolyte precursor material, and the remaining steps are the same. The different components and test results are shown in Table 4.

[0079] Table 4 Comparative Examples 1 to 3 and Examples 14 to 18 group distribution ratios and test results

[0080]

[0081]

[0082] As shown in Table 4, in the preparation method of the solid electrolyte provided by the present invention, different amounts of PEGDA used will lead to changes in ionic conductivity. An increase in the amount of PEGDA used will lead to a decrease in ionic conductivity. However, if the amount used is insufficient, the electrolyte will not solidify, and an excessive amount will lead to insufficient toughness of the electrolyte. The results are as follows: Figure 5 As shown, Figure 5 a in the equation is the electrochemical impedance spectroscopy. Figure 5 b in the figure is a real picture (Comparative Examples 1 to 3 are recorded as 0g, 0.1g, 0.2g, and 0.3g, respectively; Examples 14 to 18 are recorded as 0.3g, 0.4g, 0.5g, 0.7g, and 0.8, respectively; and Example 1 is recorded as 0.6g). Figure 5 It can be seen that when the amount of PEGDA used is small, the electrolyte precursor does not solidify. As the amount used increases, its degree of solidification begins to increase, and the solid electrolyte becomes complete. However, when the amount used is too much, its toughness decreases, making the solid electrolyte brittle.

[0083] Application Example 1

[0084] Only the light curing time of Example 1 is adjusted to 20s to obtain a solid electrolyte precursor material. The polythiophene derivative electrochromic layer and the poly 3,4-ethylenedioxythiophene / polystyrene sulfonate ion storage layer are attached to the indium tin oxide transparent conductive layer 1 and the indium tin oxide transparent conductive layer 2. A glue frame is pasted around the transparent conductive layer 2 of the transparent conductive electrode 2 containing the ion storage layer. The thickness of the glue frame is 0.3mm. The above-mentioned solid electrolyte precursor material is evenly applied to the glue frame, and then the surface of the transparent conductive layer 1 of the transparent conductive electrode 1 containing the electrochromic layer is covered on the glue frame, so that the transparent conductive electrode 1 and the transparent conductive electrode 2 are attached and form a closed space with the glue frame, and finally placed under the ultraviolet lamp conditions of Example 1 for curing to obtain a solid-state electrochromic device. A full-band transmittance test was carried out, using the electrochemical workstation and ultraviolet spectrometer combined technology. The electrochemical workstation was set to constant potential electrolysis, and the ultraviolet spectrum was set to full-band absorbance, and the scanning range was 280-800nm. The test results are as follows Figure 6 As shown, from Figure 6 It can be seen that as the voltage increases, the device begins to fade. When the voltage is 1.0V, the device reaches a completely faded state. The device in the faded state has basically no absorption in the visible light region and the device is highly transparent, which depends on the colorless and highly transparent solid electrolyte.

[0085] Corresponding to the response speed of the solid-state electrochromic device prepared in Example 1, we used the electrochemical workstation and UV spectrometer combined technology, and the electrochemical workstation was set to the multi-potential step method: the UV spectrum was set to spectral dynamics, the wavelength was set to 547nm; the initial potential was -0.6V, the end potential was 1.0V, and the potential pulse width was 3s. The test results are as follows Figure 7As shown, from Figure 7 It can be seen that the response time is 2.7s (coloring time) and 1.5s (fading time).

[0086] For the stability of the solid-state electrochromic device prepared in Example 1, we used an electrochemical workstation and a UV spectrometer. The electrochemical workstation was set to a multi-potential step method: the UV spectrum was set to spectral dynamics, and the wavelength was set to 547nm; the initial potential was -0.6V, the end potential was 1.0V, the potential pulse width was 3s, and the scanning time was 6000s. The test results are as follows Figure 8 As shown, from Figure 8 It can be seen that after 1000 cycles, the optical contrast of the device has basically not decayed, which also reflects the effectiveness and stability of the solid electrolyte.

[0087] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0088] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a photocurable solid electrolyte, characterized in that: The steps include: 1) mixing an acrylate crosslinking agent, vinyl ethylene carbonate, an ionic salt, an ionic liquid and a photoinitiator to obtain an electrolyte precursor material; 2) The electrolyte precursor material undergoes a photocuring reaction to obtain a photocurable solid electrolyte.

2. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The mass ratio of the acrylate crosslinking agent, vinyl ethylene carbonate, ionic salt, ionic liquid and photoinitiator in the electrolyte precursor material is 0.3-1: 0.3-1.5: 0-0.8: 0-1: 0.05-0.6, wherein the added amounts of the ionic salt and the ionic liquid are not zero.

3. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The acrylate crosslinking agent is one or more of ethoxylated trimethylolpropane triacrylate and polyethylene glycol diacrylate.

4. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The ionic salt is lithium bis(trifluoromethanesulfonyl)imide.

5. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The ionic liquid is 1-vinyl-3-butyl imidazole trifluoromethanesulfonyl imide salt.

6. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The photoinitiator includes 2-hydroxy-2-methyl-1-phenylpropanone and / or (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.

7. The method for preparing a photocurable solid electrolyte according to claim 1, characterized in that: The photocuring reaction is curing under ultraviolet light, the power of the ultraviolet light is 12 to 18 W, and the photocuring reaction time is 5 to 90 seconds.

8. The photocurable solid electrolyte prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the photocurable solid electrolyte according to claim 8 in an electrochromic device, characterized in that: The electrochromic device comprises a transparent conductive electrode 1, an electrochromic layer, an electrolyte layer, an ion storage layer, and a transparent conductive electrode 2 which are arranged in sequence; The electrolyte layer is a photocurable solid electrolyte.

Citation Information

Cited By

  • Lithium-salt-free gel material, electrochromic device and application

    CN121427014A